A model for ultra low cycle fatigue damage prediction of structural steel. (December 2021) - Tian, Qin; Xie, Xu; Li, Shuailing
Abstract: Ultra low cycle fatigue (ULCF) damage of structural steel is an important failure mode in earthquakes. A modified continuum damage mechanics (CDM) model was proposed to predict the fatigue life for ULCF damage. To this end, the functional form of the reduction coefficient considering the effect of plastic strain was constructed. The constant of function form was fitted by ULCF tests and genetic algorithm. Finally, the accuracy of the modified CDM model was verified by ULCF tests. Results showed that the modified CDM model could reduce the relative error between the predicted and tested fatigue life. Graphical abstract: Unlabelled Image Highlights: A modified continuum damage mechanics (CDM) model considering the effect of equivalent plastic strain on damage increment was proposed. The modified CDM model can predict the location of crack initiation. Compared with the conventional CDM model and cyclic void growth model, the modified CDM model can predict fatigue life of structural steels more accurately.